PROTOTYPE BUKA TUTUP PALANG PINTU AIR BENDUNGAN OTOMATIS BERBASIS PLC KONFIGURASI HMI - Rizki Faulianur; Rouhillah; Bariq Fajar Musaid (Politeknik Aceh, 2021)
In the dam there is a sluice gate that functions to hold water and regulate the volume of water in the dam. So far, the dam gate has been controlled manually by humans so that the water volume does not exceed the limit. The manual system requires humans to always monitor the water level of the dam. The purpose of this research is to make a prototype system for opening and closing the floodgates of the dam automatically to facilitate humans in the process of opening and closing the bars. This prototype uses an Omron PLC as the main controller, two level sensors to provide information on the water volume level, a red indicator light and a buzzer as an indicator that the water has crossed the limit, a green indicator light as an indicator of the water has dropped, and a DC motor as a dam door driver. This prototype is equipped with a Human Machine Interface (HMI) as a display on a laptop screen. The results of this prototype test, the dam door can be controlled according to water level conditions. The dam door will open automatically when the water level has reached the maximum limit, and the dam door will close again when the lower level sensor is detected. The process that occurs can be displayed on the laptop screen with an HMI simulation.